Trinity, revelation, and reading : a theological introduction to the Bible and its interpretation - Swain, Scott R. (London ; New York : T & T Clark, 2011)
"Trinity, Revelation, and Reading (TRR) is a theological introduction to the Bible and biblical interpretation. The overarching thesis is that neither the Bible nor biblical hermeneutics can be understood or practiced properly apart from an appreciation of their relationship to the triune God and his gracious economy of redemption. Scott Swain treats the role of the Word in the saving economy of the triune God, the role and status of Scripture as the Word of God, the nature of biblical reading as a covenantal enterprise, as well as a host of other related topics. These topics are addressed by way of a constructive appropriation, or ressourcement, of many of the themes of patristic theology and early Protestant divinity (esp. Reformed Orthodoxy), while building upon the work of important contemporary theologians as well (e.g., Karl Barth, John Webster, Kevin Vanhoozer). The ultimate goal of this study is that readers will appreciate better the ways in which biblical interpretation is an aspect of their covenantal engagement with the triune God." -- Publisher's description.
The Trinity, the kingdom, and the historical progression of the Word of God -- The role of Holy Scripture in kingdom and covenant -- The inspiration and perfection of Holy Scripture -- Reading as an act of covenant mutuality, part one : regeneration, renewal, and the role of the church -- Reading as an act of covenant mutuality, part two : the practice of reading and the shape of interpretation.
Includes bibliographical references (pages 141-150) and index.
Keywords: Bible -- Criticism, interpretation, etc